A high-hardness self-cleaning antifouling resin, coating and preparation method and application thereof

By using silicone and long-chain acrylate monomers in the coating, combined with long-chain alkyl modified hydrogen-containing silicone oil and hyperbranched silicone resin, the existing fluorocarbon coatings are easily discolored and stained in urban environments, and high-hardness, weather-resistant self-cleaning and anti-fouling coatings are achieved, suitable for modern high-end construction needs.

CN119775480APending Publication Date: 2025-04-08INST OF CHEM ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411946523.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing fluorocarbon coatings are prone to discoloration and staining problems in urban environments, and are difficult to meet the needs of modern high-end urban buildings for functions such as stain-resistant self-cleaning, antibacterial and mildew-proof, and graffiti-proof. At the same time, their poor fire resistance and environmental non-degradation also have safety and environmental protection problems.

Method used

Copolymerization of reactive silicone and long-chain acrylate monomers was used to obtain the coated main resin, and through organic-inorganic hybridization technology, combined with long-chain alkyl modified hydrogen-containing silicone oil and hyperbranched silicone resin, a high-hardness, weather-resistant self-cleaning, and anti-fouling fluorine-free transparent coating was prepared.

Benefits of technology

It has achieved long-term effective high hardness, weather-resistant self-cleaning and corrosion-proof functions, and improved the wear resistance, scratch resistance and flexibility of the coating. It also has low surface energy, low adhesion and excellent anti-fouling and anti-fouling self-cleaning effects, suitable for high-end construction and industrial fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775480A_ABST
    Figure CN119775480A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of coating chemical industry, and specifically discloses a high-hardness self-cleaning antifouling resin, coating, and preparation method and application thereof. The raw material components of the resin include by weight: 2-10 parts of a first monomer, 25-40 parts of a second monomer, 3-20 parts of a third monomer, 0.5-1 parts of an initiator, 0.1-0.5 parts of a chain transfer agent, and 46-50 parts of a first solvent; wherein: the first monomer is an aminoacrylic acid monomer, the second monomer is a long-chain acrylate monomer, and the third monomer is an organosilicon monomer. The coating prepared by the present invention can achieve long-term and effective functions such as high hardness, weather-resistant self-cleaning and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating chemical industry, and specifically relates to a high-hardness self-cleaning and anti-fouling resin, coating, and a preparation method and application thereof. Background Art

[0002] With the advancement of industrial technology and the improvement of people's living standards, higher requirements are placed on the surface properties of materials such as long-term stain resistance, self-cleaning, corrosion resistance, and anti-fouling in clothing, food, housing, transportation, and industrial applications. Surfaces with anti-fouling or self-cleaning properties, such as resistance to chemical and physical bonding of dust particles and other types of stains, are not only crucial for photovoltaic modules and solar thermal systems, but also for general purposes, such as preventing fingerprint marks and stains on smartphones or graffiti on walls, and making these surfaces easy to clean when they are dirty. Anti-fouling, anti-fouling and anti-corrosion properties are widely sought after properties of coatings. Low surface energy coatings have low surface energy (film surface energy <25mN / m), so dust, oil stains, fouling organisms, etc. have weak binding force on the coating surface and are difficult to adhere to. Even if they are attached, they can be easily removed by rain washing or other mechanical methods, reflecting a self-cleaning or easy-to-clean effect.

[0003] The antifouling properties of certain inert organic molecules such as polymers are related to the coefficient of friction (CoF). The lower the coefficient of friction, the smoother the surface of an object. For example, a low-friction surface is easier to clean any dirt that accumulates on it with little or no mechanical damage to the surface. For example, larger particles such as sand in a sandstorm can bounce off a high-hardness smooth surface without causing significant wear. In addition, a low-friction smooth surface can effectively enhance people's smooth experience of smartphone screens and car touch screens. Currently, fluorinated silicone oligomers are commonly used in the surface treatment of high-end smartphone screens to obtain this soft, smooth feeling as well as good anti-fingerprint and anti-fouling properties.

[0004] In addition, coatings with a low refractive index are needed. The refractive index is the most fundamental quantity in optics and optoelectronics, and it determines many quality factors of optical components such as reflectors, filters and resonators. It determines the focusing power of lenses, the dispersion power of prisms, the reflectivity of lens coatings, and the light-guiding properties of optical fibers. When entering a medium with a low refractive index, light deviates from the normal and refracts toward the surface of the medium.

[0005] Hot-melt fluorocarbon coatings with PVDF (polyvinylidene fluoride) as the main film-forming material have a history of more than 50 years in the field of architectural decoration. With the advantages of diverse colors and ultra-long weather resistance (outdoor for more than 15 years), they are widely used in high-rise building exterior walls, gymnasiums, airports, exhibition halls, cross-sea bridges, power plants, chemical storage tanks and other fields, and occupy an absolute dominant position. However, due to the rough surface and high surface energy (≥38mN / m) of conventional fluorocarbon coatings, coupled with the increase of pollutants such as urban dust, oil smoke, acid rain, and chemical dust, the surface of fluorocarbon coatings is prone to discoloration and staining. It does not have the functions of stain resistance, self-cleaning, antibacterial and mildew-proof, and anti-graffiti, and can no longer meet the needs of modern high-end urban buildings. In addition, fluorocarbon coatings have poor fire resistance and will produce fluorine-containing toxic gases when burned at high temperatures. As a building decoration material, it is not conducive to fire safety. Fluorocarbon coatings are difficult to degrade in the environment. It takes more than 100 years to completely degrade in the environment. They are prone to microplastic pollution in soil, water bodies, etc., which imposes a great environmental and cost burden on post-use treatment. At the same time, due to the increasing environmental protection requirements at home and abroad, the ban of fluorocarbon polymers in multiple fields has gradually become a trend.

[0006] In addition, the pencil hardness of conventional coatings is generally between HB-2H, with poor wear resistance and scratch resistance. Conventional coatings are difficult to meet actual needs in photovoltaic panels, wind turbine blades, EMU locomotive heads, security cameras that have high requirements for resistance to external impact in outdoor windy and sandy environments, as well as smart appliance screens, marble tea tables, floor ceramics, stainless steel sinks, non-stick pans, bathrooms, etc., which have high requirements for material surface hardness and have urgent needs for self-cleaning, anti-fouling and safe fluoride-free material surfaces.

[0007] Therefore, the development of fluorine-free transparent coatings that combine high hardness, weather resistance, self-cleaning and anti-fouling for application in the industrial and furniture fields is an urgent problem to be solved. Summary of the invention

[0008] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a high-hardness self-cleaning antifouling resin, a coating and a preparation method and application thereof, wherein the coating can achieve long-term effective high hardness, weather-resistant self-cleaning and anti-corrosion functions.

[0009] To solve the above technical problems, the first aspect of the present invention provides a resin, wherein the raw material components of the resin include, by weight: 2-10 parts of a first monomer, 25-40 parts of a second monomer, 3-20 parts of a third monomer, 0.5-1 parts of an initiator, 0.1-0.5 parts of a chain transfer agent, and 46-50 parts of a first solvent; the first monomer is an aminoacrylic acid monomer, the second monomer is a long-chain acrylate monomer, and the third monomer is a silicone monomer.

[0010] Preferably, the aminoacrylic acid monomer is selected from at least one of tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, dipropylaminoethyl methacrylate, diisopropylaminoethyl methacrylate, dibutylaminoethyl methacrylate and di-tert-butylaminoethyl methacrylate;

[0011] Preferably, the acrylic acid ester monomer is selected from at least one of n-octyl methacrylate, n-octyl acrylate, isooctyl methacrylate, isooctyl acrylate, isobutyl methacrylate, isobutyl acrylate, lauryl methacrylate, lauryl acrylate, isotridecyl methacrylate, isotridecyl acrylate, heptadecyl methacrylate, heptadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, and behenyl acrylate.

[0012] Preferably, the silicone monomer is selected from at least one of γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-methacryloxypropyl methyl dimethoxysilane, γ-methacryloxypropyl methyl diethoxysilane, γ-acetoxypropyl trimethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl triisopropoxysilane, and 3-(isomethacryloxy)propyl tris(trimethylsiloxane)silane. Further preferably, the silicone monomer is selected from at least one of γ-methacryloxypropyl triethoxysilane, γ-methacryloxypropyl methyl diethoxysilane, and 3-(isomethacryloxy)propyl tris(trimethylsiloxane)silane.

[0013] Preferably, the initiator is selected from at least one of 2,2'-azobis(2-methylpropionitrile) and 2,2'-disazo-(2,4-dimethylvaleronitrile).

[0014] Preferably, the chain transfer agent is selected from at least one of n-dodecyl mercaptan, secondary dodecyl mercaptan, tert-dodecyl mercaptan, cyclohexyl mercaptan, isooctyl 3-mercaptopropionate, n-butyl 3-mercaptopropionate, n-octyl mercaptan, mercaptoethanol, and thioglycolic acid; further preferably, the chain transfer agent is selected from at least one of n-dodecyl mercaptan, isooctyl 3-mercaptopropionate, and n-butyl 3-mercaptopropionate.

[0015] Preferably, the first solvent is selected from at least one of ether solvents, ester solvents, and ketone solvents; more preferably, the first solvent is selected from at least one of propylene glycol methyl ether acetate, a dibasic acid ester mixture (DBE), and propylene glycol dimethyl ether.

[0016] The second aspect of the present invention provides a method for preparing the above resin, comprising the following steps:

[0017] The first solvent and the initiator are divided into three parts respectively, and one part of the first solvent and one part of the initiator are first mixed and heated; then another part of the first solvent, another part of the initiator, the first monomer, the second monomer and the third monomer are added to react; then the remaining first solvent and the remaining initiator are added to continue the reaction; finally, a chain transfer agent is added, the temperature is lowered, and the resin is obtained.

[0018] Preferably, the heating temperature is 70-85° C.; more preferably, the heating temperature is 75-80° C. Before adding the chain transfer agent, the material system is maintained at this temperature for addition and reaction.

[0019] Preferably, the temperature is lowered to 20-30°C.

[0020] Preferably, the reaction time is 2-4 hours; more preferably, the reaction time is 2.5-3.5 hours.

[0021] Preferably, the continued reaction time is 1-3 hours; more preferably, the continued reaction time is 1.5-2.5 hours.

[0022] Preferably, during the process of adding the first solvent, the first addition amount accounts for 8-12% of the total mass of the first solvent; and the second addition amount accounts for 78-82% of the total mass of the first solvent.

[0023] Preferably, during the process of adding the initiator, the first addition amount accounts for 8-12% of the total mass of the initiator; and the second addition amount accounts for 78-82% of the total mass of the initiator.

[0024] Preferably, the first monomer, the second monomer and the third monomer are added dropwise, and the total time of the addition is 1.5-2.5 hours.

[0025] The third aspect of the present invention provides a coating, wherein the raw material components of the coating include, by weight: 10-20 parts of the above-mentioned resin, 10-20 parts of long-chain alkyl-modified hydrogenated silicone oil, 10-30 parts of a silane coupling agent, 1-3 parts of a hyperbranched silicone resin, and 0.3-2 parts of a long-chain alkyl-modified polysilazane.

[0026] Preferably, the structural formula of the long-chain alkyl-modified hydrogen-containing silicone oil is as shown in formula (1):

[0027]

[0028] In formula (1): x=0-500, y=1-500, z=1-25;

[0029] P is selected from a C8-C18 straight chain alkyl group, a C8-C18 branched chain alkyl group, a C8-C18 cycloalkyl group or a C8-C18 aralkyl group.

[0030] Preferably, the silane coupling agent is selected from at least one of tetraethyl silicate, tetramethyl silicate, trimethoxysilane, triethoxysilane, vinyl triisopropoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl triisopropoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-glycidyloxypropyl triisopropoxysilane, octyl trimethoxysilane, octyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, octadecyl trimethoxysilane, octadecyl triethoxysilane, and long-chain quaternary ammonium salt silane; the structural formula of the long-chain quaternary ammonium salt silane is shown in formula (2):

[0031]

[0032] In formula (2): R 1 An alkyl group selected from C8-C18, R 2 Selected from CH 3 or CH 2 CH 3 .

[0033] Preferably, the structural formula of the hyperbranched silicone resin is as shown in formula (3):

[0034]

[0035] In formula (3), R is at least one selected from γ-glycidyloxypropyl, γ-aminopropyl and hydrogen.

[0036] Preferably, the structural formula of the long-chain alkyl-modified polysilazane is as shown in formula (4):

[0037]

[0038] In formula (4): a=3-500, b=3-500, c=1-100;

[0039] R 3 Selected from C8-C18 straight chain alkyl or C8-C18 branched chain alkyl.

[0040] Preferably, the raw material components of the coating further include at least one of a catalyst, a light stabilizer, an ultraviolet light absorber, and a second solvent.

[0041] Preferably, the raw material components of the coating further include, by weight: 0.01-1 parts of a catalyst, 0.5-1.5 parts of a light stabilizer, 1-3 parts of an ultraviolet light absorber, and 40-46 parts of a second solvent.

[0042] Preferably, the catalyst is selected from at least one of an organic tin catalyst, an organic bismuth catalyst, an organic titanium catalyst, an acidic compound catalyst, and a basic compound catalyst.

[0043] Preferably, the organotin catalyst is selected from at least one of dibutyltin dilaurate, di-n-octyltin dilaurate, dimethyltin dilaurate, dibutyltin diacetate, dimethyltin diacetate, stannous octoate, dioctyltin, monobutyltin oxide, dibutyltin oxide, and dibutyltin maleate.

[0044] Preferably, the organic bismuth catalyst is selected from at least one of bismuth neodecanoate, bismuth laurate, bismuth isooctanoate and bismuth cyclohexaneate.

[0045] Preferably, the organic titanium catalyst is selected from ethyl acetoacetate titanium and / or tetrabutyl titanate.

[0046] Preferably, the acidic compound catalyst is selected from at least one of acrylic acid, methacrylic acid, maleic acid, acetic acid, hydrochloric acid, p-toluenesulfonic acid, phosphorous acid, phosphoric acid and esters thereof.

[0047] Preferably, the alkaline compound catalyst is selected from at least one of triethanolamine, diethanolamine, monoethanolamine, triethylamine, N,N-dimethylcyclohexylamine, triethylenediamine, and tetramethylguanidine (TMG).

[0048] Preferably, the light stabilizer is selected from hindered amine light stabilizers; further preferably, the hindered amine light stabilizer is selected from BASF Tinuvin 292.

[0049] Preferably, the ultraviolet light absorber is selected from benzotriazole ultraviolet light absorbers; further preferably, the benzotriazole ultraviolet light absorber is selected from BASF Tinuvin 1130.

[0050] Preferably, the second solvent is selected from at least one of benzene solvents, ether solvents, ester solvents, and cyclosiloxane solvents. Further preferably, the second solvent is selected from at least one of toluene, xylene, butyl acetate, ethyl acetate, amyl acetate, isooctyl acetate, ethylene glycol butyl ether acetate, ethylene glycol diacetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol dimethyl ether, dimethyl succinate, dimethyl glutarate, dimethyl adipate, dimethyl phthalate, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane.

[0051] A fourth aspect of the present invention provides a method for preparing the above-mentioned coating, comprising the following steps:

[0052] The various raw materials for preparing the coating are mixed to obtain the coating.

[0053] Preferably, the mixing method is stirring, and the stirring speed is 50-400r / min; preferably, the stirring speed is 100-200r / min.

[0054] Preferably, the mixing temperature is 5-40°C; further preferably, the mixing temperature is 10-30°C; further preferably, the mixing temperature is 15-25°C.

[0055] Preferably, the relative humidity of the environment during mixing is less than 70% RH; further preferably, the relative humidity of the environment during mixing is less than 60% RH; further preferably, the relative humidity of the environment during mixing is less than 50% RH.

[0056] Preferably, the mixing time is 5-40 min; more preferably, the mixing time is 15-30 min.

[0057] A fifth aspect of the present invention provides a coating formed by curing the above-mentioned coating.

[0058] Preferably, the curing temperature is 5-60°C; further preferably, the curing temperature is 15-50°C; further preferably, the curing temperature is 25-40°C.

[0059] Preferably, the curing time is 3 minutes to 24 hours; further preferably, the curing time is 5 minutes to 2 hours; further preferably, the curing time is 10 minutes to 2 hours.

[0060] Preferably, the coating curing method comprises the following steps: spraying or scraping the coating onto the surface of a carrier, and curing the coating to obtain the coating.

[0061] Preferably, the coating has a thickness of 3-30 μm.

[0062] A sixth aspect of the present invention provides the application of the above-mentioned paint or coating in the fields of construction, new energy, transportation, home, communication or mechanical equipment.

[0063] Preferably, the paint or coating can achieve a permanent anti-fingerprint function on the surface of the electronic screen, meeting the requirements for photovoltaic panels, wind turbine blades, EMU locomotive heads, and security cameras in outdoor windy and sandy environments with high requirements for resistance to foreign object impact, as well as smart appliance screens, marble tea tables, floor ceramics, stainless steel sinks, non-stick pans, bathrooms, and other fields that have high requirements for material surface hardness and have an urgent need for self-cleaning, anti-fouling, and safe, fluorine-free material surfaces, to achieve a long-lasting anti-fouling and self-cleaning effect.

[0064] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0065] (1) The present invention uses a reactive organic silicon and a long-chain acrylate monomer with a long hydrophobic group to copolymerize to obtain the main resin of the coating. The introduction of the long carbon chain group increases the hydrophobicity of the resin and the system compatibility of the long-chain alkyl-modified hydrogenated silicone oil, thereby obtaining a more uniform and dense coating. At the same time, the introduction of the aminoacrylic acid monomer can effectively improve the substrate adhesion of the resin and the ability of the moisture-catalyzed rapid curing reaction, and synergistically enhance the reactivity of the system with the long-chain alkyl-modified hydrogenated silicone oil, which can effectively reduce the curing temperature required for the coating to cure and shorten the curing time.

[0066] (2) The present invention adopts organic-inorganic hybrid technology to obtain a high-density coating with a pencil hardness of 6-7H, which greatly improves the wear resistance and scratch resistance of the coating. At the same time, the resin with a specific structure and the long-chain alkyl-modified hydrogenated silicone oil enhance the flexibility and hydrophobic antifouling property of the coating, and polymerizes with the silane coupling agent and the long-chain alkyl-modified polysilazane to form a film, thereby obtaining high hardness and weather resistance, excellent low adhesion properties, scratch resistance and wear resistance, low surface roughness and high gloss on the painted surface, thereby realizing a permanent anti-fingerprint function on the surface of the electronic screen.

[0067] (3) The present invention uses long-chain alkyl-modified hydrogen-containing silicone oil and long-chain alkyl-modified polysilazane for synergistic enhancement. By introducing Si-H bonds and NH bonds, the two interact with each other to enhance the reaction speed and crosslinking density of the coating system under the action of moisture. At the same time, by introducing long-chain alkyl groups, the thermal stability, high and low temperature resistance, impact resistance and water resistance of the coating are effectively improved.

[0068] (4) The present invention uses a variety of silane coupling agents and hyperbranched silicone resins to work together to form long-chain alkyl-modified hydrogenated silicone oil, thereby improving the substrate adhesion, crosslinking density and moisture reactivity of the coating, solving the problem of poor substrate adhesion of the alkyl-modified hydrogenated silicone oil, and at the same time providing a dense "skeleton" for the coating, greatly reducing the dynamic friction coefficient of the coating to between 0.02 and 0.03, reducing the damage to the coating caused by external forces, and obtaining an ultra-smooth and scratch-resistant surface.

[0069] (5) The coating of the present invention does not contain fluorine element and has a hydrophobic, anti-fouling and self-cleaning effect, thereby improving the safety of the product.

[0070] (6) The coating of the present invention adopts a single-component room temperature moisture curing solution, which can be quickly cross-linked and cured at room temperature, providing great convenience for outdoor operations without baking conditions and working conditions with strict time limits on the construction cycle. The single-component solution also reduces construction complexity, saves manpower and energy loss, and improves work efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is the infrared spectrum of the resin prepared in Example 1 of the present invention;

[0072] Figure 2 This is the initial water contact angle of the coating prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0073] The present invention is described in detail below in conjunction with the embodiments, so as to facilitate the understanding of the present invention by those skilled in the art. It is necessary to point out here that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by those skilled in the art according to the above invention content should still fall within the scope of protection of the present invention.

[0074] Meanwhile, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not described in detail are all process steps or preparation methods known to those skilled in the art. Among them, the purchase of some reagents and raw materials is as follows:

[0075] Hyperbranched silicone resin and long-chain alkyl-modified polysilazane: purchased from Guangdong Jinbo Chemical Co., Ltd.;

[0076] Long-chain alkyl-modified hydrogen-containing silicone oil: purchased from Guangzhou Fuze New Materials Co., Ltd.

[0077] Example 1

[0078] A method for preparing a resin comprises the following steps:

[0079] 50 grams of propylene glycol methyl ether acetate and 1 gram of 2,2'-azobis(2-methylpropionitrile) are mixed, heated to 70 ℃, 400 grams of propylene glycol methyl ether acetate, 8 grams of 2,2'-azobis(2-methylpropionitrile), 30 grams of tert-butylaminoethyl methacrylate, 200 grams of isotridecyl methacrylate, 150 grams of octadecyl methacrylate, 30 grams of gamma-methacryloxypropyl triethoxysilane and 50 grams of 3-(isobutylene acyloxy)propyl tris(trimethylsiloxane) silane are added dropwise for 2 hours; The reaction is maintained at 80 ℃ for 3 hours, then 50 grams of propylene glycol methyl ether acetate and 1 gram of 2,2'-azobis(2-methylpropionitrile) are added, the reaction is maintained at 80 ℃ for 2 hours, 5 grams of isooctyl 3-mercaptopropionate are added, and the temperature is cooled to 25 ℃ to obtain the resin of the present embodiment.

[0080] Figure 1 The infrared spectrum of the resin obtained in Example 1 is as follows: Figure 1 The infrared spectrum analysis results show that: 2921cm -1 and 2851cm -1 The corresponding is -CH 3 and -CH 2 -Stretching vibration absorption peak; 3544cm -1 The corresponding peak is the stretching vibration absorption peak of -NH-; 1731cm -1 It is the asymmetric stretching vibration absorption peak of the C=O bond on the ester group, which comes from the C=O absorption peak of acrylic resin; 1151cm -1 The asymmetric stretching peak of COC is at 1060cm -1 is the Si-O-Si absorption peak, 1250cm -1 、844cm -1 and 756cm -1 Si-CH 3 Characteristic absorption peaks indicate that the organosilicon monomer participates in the polymerization reaction, and the 1680cm -1 The C=C stretching vibration peak indicates that the monomer polymerization is basically completed, confirming that the desired resin structure is obtained.

[0081] Example 2

[0082] A method for preparing a resin comprises the following steps:

[0083] 20.8 g of DBE, 16 g of propylene glycol dimethyl ether and 0.5 g of 2,2'-azobis(2-methylpropionitrile) were mixed and heated to 75°C, 213.2 g of DBE, 164 g of propylene glycol dimethyl ether, 4 g of 2,2'-azobis(2-methylpropionitrile), 100 g of diethylaminoethyl methacrylate, 150 g of n-octyl methacrylate, 250 g of lauryl methacrylate and 30 g of gamma-methacryloxypropyltriethoxysilane were added dropwise for 2 hours; the reaction was maintained at 80°C for 3 hours, then 26 g of DBE, 20 g of propylene glycol dimethyl ether and 0.5 g of 2,2'-azobis(2-methylpropionitrile) mixture was added, the reaction was maintained at 80°C for 2 hours, 3 g of n-dodecyl mercaptan was added and the temperature was cooled to 25°C to obtain the resin of the present embodiment.

[0084] The infrared spectrum of the resin prepared in Example 2 has similar characteristics to the infrared spectrum of the resin prepared in Example 1.

[0085] Example 3

[0086] A method for preparing a resin comprises the following steps:

[0087] 36 g of propylene glycol dimethyl ether, 24 g of propylene glycol methyl ether acetate and 0.72 g of 2,2'-bisazo-(2,4-dimethylvaleronitrile) were mixed and heated to 70°C, 234 g of propylene glycol dimethyl ether, 156 g of propylene glycol methyl ether acetate and 7.38 g of 2,2'-bisazo-(2,4-dimethylvaleronitrile), 20 g of diisopropylaminoethyl methacrylate, 370 g of lauryl methacrylate and 100 g of γ-methacryloxypropylmethyldiethoxysilane were added dropwise for 2 hours; the reaction was maintained at 75°C for 3 hours, and then 30 g of propylene glycol dimethyl ether, 20 g of propylene glycol methyl ether acetate and 0.9 g of 2,2'-bisazo-(2,4-dimethylvaleronitrile) mixture were added, the reaction was maintained at 80°C for 2 hours, 1 g of n-butyl 3-mercaptopropionate was added, and the temperature was lowered to 25°C to obtain the resin of the present embodiment.

[0088] The infrared spectrum of the resin prepared in Example 3 has similar characteristics to the infrared spectrum of the resin prepared in Example 1.

[0089] Example 4

[0090] A method for preparing a resin comprises the following steps:

[0091] 49.2 g of propylene glycol methyl ether acetate and 0.6 g of 2,2'-disazo-(2,4-dimethylvaleronitrile) were mixed and heated to 70°C, 393.6 g of propylene glycol methyl ether acetate, 3.9 g of 2,2'-disazo-(2,4-dimethylvaleronitrile), 50 g of di-tert-butylaminoethyl methacrylate, 100 g of isobutyl methacrylate, 150 g of behenyl acrylate and 2003-(isobutylene acyloxy)propyl tris(trimethylsiloxane)silane were added dropwise for 2 hours; the reaction was maintained at 80°C for 3 hours, and then 49.2 g of propylene glycol methyl ether acetate and 0.5 g of 2,2'-azobis(2-methylpropionitrile) mixture were added, the reaction was maintained at 75°C for 2 hours, 3 g of n-dodecyl mercaptan was added, and the temperature was lowered to 25°C to obtain the resin of the present embodiment.

[0092] The infrared spectrum of the resin prepared in Example 4 has similar characteristics to the infrared spectrum of the resin prepared in Example 1.

[0093] Example 5

[0094] A method for preparing a coating comprises the following steps:

[0095] (1) Stirring the raw materials of the coating at room temperature at a speed of 200 r / min for 15 min to obtain the coating; wherein the raw material components of the coating are: 100 g of the resin obtained in Example 1, 150 g of a long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=100, y=400, z=10; P is a C12 straight-chain alkyl], 20 g of tetraethyl silicate, 200 g of γ-glycidyloxypropyltriethoxysilane, 80 g of dodecyltrimethoxysilane, 20 g of a hyperbranched silicone resin [the structural formula is shown in formula (3), and R is γ-aminopropyl], and 20 g of a long-chain alkyl-modified polysilazane [the structural formula is shown in formula (4), and a=2, b=50, c=8, R 3 [C8 straight chain alkyl] 3 grams, dibutyltin dilaurate 0.3 grams, triethylamine 7.7 grams, light stabilizer 9 grams, ultraviolet light absorber 10 grams, butyl acetate 100 grams, octamethylcyclotetrasiloxane 300 grams;

[0096] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 40° C. for 10 min to obtain a coating with a film thickness of 3 μm in this embodiment.

[0097] Example 6

[0098] A method for preparing a coating comprises the following steps:

[0099] (1) Stirring the raw materials of the coating at room temperature at a speed of 100 r / min for 30 min to obtain a coating; wherein the raw materials of the coating are composed of: 200 g of the resin obtained in Example 2, 100 g of a long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=0, y=500, z=25; P is a branched alkyl group of C13], 20 g of tetraethyl silicate, 130 g of γ-glycidyloxypropyltriethoxysilane, 50 g of γ-aminopropyltrimethoxysilane, 50 g of octyltriethoxysilane, 10 g of a hyperbranched silicone resin [the structural formula is shown in formula (3), and R is γ-aminopropyl], and 10 g of a long-chain alkyl-modified polysilazane [the structural formula is shown in formula (4), and a=100, b=500, c=50, R 3 [C18 linear alkyl] 10 g, stannous octoate 0.1 g, light stabilizer 9.9 g, ultraviolet light absorber 20 g, octamethylcyclotetrasiloxane 400 g;

[0100] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 35° C. for 30 min to obtain a coating with a film thickness of 10 μm in this embodiment.

[0101] Example 7

[0102] A method for preparing a coating comprises the following steps:

[0103] (1) Stirring the raw materials of the coating at room temperature at a speed of 200 r / min for 20 min to obtain the coating; wherein the raw materials of the coating are composed of: 150 g of the resin obtained in Example 3, 150 g of a long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=10, y=100, z=5; P is a C18 aralkyl], 20 g of tetraethyl silicate, 80 g of γ-glycidyloxypropyltriisopropoxysilane, 20 g of γ-aminopropyltriisopropoxysilane, 80 g of dodecyltrimethoxysilane, 20 g of a hyperbranched silicone resin [the structural formula is shown in formula (3), and R is hydrogen], 20 g of a long-chain alkyl-modified polysilazane [the structural formula is shown in formula (4), and a=5, b=300, c=20, R 3 [C13 branched alkyl] 20 grams, ethyl acetoacetate titanium 0.5 grams, N, N-dimethylcyclohexylamine 9.5 grams, light stabilizer 15 grams, ultraviolet light absorber 15 grams, xylene 120 grams, octamethylcyclotetrasiloxane 300 grams;

[0104] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 30° C. for 1 h to obtain a coating with a film thickness of 30 μm in this embodiment.

[0105] Example 8

[0106] A method for preparing a coating comprises the following steps:

[0107] (1) Stirring the raw materials of the coating at room temperature at a speed of 150 r / min for 20 min to obtain the coating; wherein the raw materials of the coating are composed of: 150 g of the resin obtained in Example 4, 200 g of a long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=5, y=200, z=2; P is a cycloalkyl group of C18], 20 g of triethoxysilane, 30 g of γ-glycidyloxypropyltriethoxysilane, 20 g of γ-aminopropyltriethoxysilane, 20 g of octadecyltriethoxysilane, and a long-chain quaternary ammonium salt silane [the structural formula is shown in formula (2), and R 1 is a C8 alkyl group, R 2 CH 2 CH 3 】10 g, hyperbranched silicone resin [structural formula as shown in formula (3), and R is γ-glycidyloxypropyl] 30 g, long-chain alkyl-modified polysilazane [structural formula as shown in formula (4), and a=500, b=500, c=100, R 3 [C16 branched alkyl] 20 grams, bismuth laurate 0.5 grams, p-toluenesulfonic acid 4.5 grams, light stabilizer 5 grams, ultraviolet light absorber 30 grams, xylene 200 grams, decamethylcyclopentasiloxane 260 grams;

[0108] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 25° C. for 2 h to obtain a coating with a film thickness of 20 μm in this embodiment.

[0109] Comparative Example 1

[0110] A method for preparing a coating comprises the following steps:

[0111] (1) Stirring the raw materials of the coating at room temperature at a speed of 100 r / min for 30 minutes to obtain a coating; wherein the raw materials of the coating are composed of: 200 g of silicone-modified epoxy acrylic resin [the structural formula is shown in formula (5), and x:y:z=1:1:1], 100 g of long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=0, y=500, z=25; P is a branched alkyl group of C13], 20 g of tetraethyl silicate, 130 g of γ-glycidyloxypropyltriethoxysilane, 50 g of γ-aminopropyltrimethoxysilane, 50 g of octyltriethoxysilane, 10 g of hyperbranched silicone resin [the structural formula is shown in formula (3), and R is γ-aminopropyl], and 10 g of long-chain alkyl-modified polysilazane [the structural formula is shown in formula (4), and a=100, b=500, c=50, R 3 [C18 linear alkyl] 10 g, stannous octoate 0.1 g, light stabilizer 9.9 g, ultraviolet light absorber 20 g, octamethylcyclotetrasiloxane 400 g;

[0112]

[0113] (2) The coating prepared in step (1) was sprayed on the glass surface, dried at room temperature for 1 hour, and then cured at 160° C. for 1 hour to obtain a coating with a film thickness of 10 μm in this comparative example.

[0114] Compared with Example 6, when preparing the coating of Comparative Example 1, a short carbon chain silicone-modified epoxy acrylic resin is used to replace the long chain alkyl and silicone co-modified amino acrylic resin of Example 2.

[0115] Comparative Example 2

[0116] A method for preparing a coating comprises the following steps:

[0117] (1) Stirring the raw materials of the coating at room temperature at a speed of 100 r / min for 30 min to obtain the coating; wherein the raw materials of the coating are composed of: 200 g of the resin obtained in Example 2, 100 g of methyl hydrogen silicone oil [the structural formula of which is shown in formula (6)], 20 g of tetraethyl silicate, 130 g of γ-glycidyloxypropyltriethoxysilane, 50 g of γ-aminopropyltrimethoxysilane, 50 g of octyltriethoxysilane, 10 g of hyperbranched silicone resin [the structural formula of which is shown in formula (3), and R is γ-aminopropyl], and 10 g of polysilazane [the structural formula of which is shown in formula (4), and a=100, b=500, c=50, R 3 [C18 linear alkyl] 10 g, stannous octoate 0.1 g, light stabilizer 9.9 g, ultraviolet light absorber 20 g, octamethylcyclotetrasiloxane 400 g;

[0118]

[0119] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 35° C. for 30 min to obtain a coating with a film thickness of 10 μm.

[0120] Compared with Example 6, when preparing the coating of Comparative Example 2, methyl hydrogen-containing silicone oil was used to replace the long-chain alkyl-modified hydrogen-containing silicone oil of Example 6.

[0121] Comparative Example 3

[0122] A method for preparing a coating comprises the following steps:

[0123] (1) Stirring the raw materials of the coating at room temperature at a speed of 200 r / min for 20 min to obtain the coating; wherein the raw materials of the coating are composed of: 150 g of the resin obtained in Example 3, 150 g of alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (1), and x=10, y=100, z=5; P is a C18 aralkyl], 20 g of tetraethyl silicate, 80 g of γ-glycidyloxypropyltriisopropoxysilane, 20 g of γ-aminopropyltriisopropoxysilane, 80 g of dodecyltrimethoxysilane, polysilazane [the structural formula is shown in formula (4), and a=5, b=300, c=20, R 3 [C13 branched alkyl] 20 grams, ethyl acetoacetate titanium 0.5 grams, N, N-dimethylcyclohexylamine 9.5 grams, light stabilizer 15 grams, ultraviolet light absorber 15 grams, xylene 120 grams, octamethylcyclotetrasiloxane 300 grams;

[0124] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 30° C. for 2 h to obtain a coating with a film thickness of 30 μm in this comparative example.

[0125] Compared with Example 7, no hyperbranched silicone resin was added during the preparation of the coating of Comparative Example 3.

[0126] Comparative Example 4

[0127] A method for preparing a coating comprises the following steps:

[0128] (1) Stirring the raw materials of the coating at room temperature at a speed of 200 r / min for 20 min to obtain the coating; wherein the raw materials of the coating are composed of: 150 g of the resin obtained in Example 3, 150 g of methyl hydrogen silicone oil [the structural formula of which is shown in formula (6)], 20 g of tetraethyl silicate, 80 g of γ-glycidyloxypropyltriisopropoxysilane, 20 g of γ-aminopropyltriisopropoxysilane, 80 g of dodecyltrimethoxysilane, 20 g of hyperbranched silicone resin [the structural formula of which is shown in formula (3) and R is hydrogen], 0.5 g of ethyl acetoacetate titanium, 9.5 g of N,N-dimethylcyclohexylamine, 15 g of a light stabilizer, 15 g of an ultraviolet light absorber, 120 g of xylene, and 300 g of octamethylcyclotetrasiloxane;

[0129] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 30° C. for 2 h to obtain a coating with a film thickness of 30 μm in this comparative example.

[0130] Compared with Example 7, when preparing the coating of Comparative Example 4, no polysilazane was added, and methyl hydrogen-containing silicone oil was used instead of the long-chain alkyl-modified hydrogen-containing silicone oil of Example 7.

[0131] Comparative Example 5

[0132] A method for preparing a coating comprises the following steps:

[0133] The raw materials of the coating were stirred at a constant speed of 200 r / min at room temperature for 20 minutes to obtain the coating; wherein: the raw materials of the coating were composed of: 150 g of the resin obtained in Example 3, 150 g of long-chain alkyl-modified hydrogenated silicone oil [the structural formula is shown in formula (7), and x=10, y=100, z=5; P is a C18 aralkyl], 20 g of tetraethyl silicate, 80 g of γ-glycidyloxypropyl triisopropoxy silane, and 20 g of γ-aminopropyl triisopropoxy silane. , 80 g of dodecyltrimethoxysilane, 20 g of hyperbranched silicone resin [the structural formula is shown in formula (3), and R is hydrogen], 20 g of DURAZANE 1800 [the structural formula is shown in formula (7), and the weight average molecular weight is 300] from Merck, Germany, 0.5 g of ethyl acetoacetate titanium, 9.5 g of N,N-dimethylcyclohexylamine, 15 g of light stabilizer, 15 g of ultraviolet light absorber, 120 g of xylene, and 300 g of octamethylcyclotetrasiloxane;

[0134]

[0135] (2) The coating prepared in step (1) was sprayed on the glass surface, and the coating film was cured at 30° C. for 1 h to obtain a coating with a film thickness of 30 μm in this embodiment.

[0136] Compared with Example 7, the coating of Comparative Example 5 is prepared by using perhydropolysilazane instead of the long-chain alkyl-modified polysilazane of Example 7.

[0137] Performance Testing

[0138] The coatings prepared in Examples 5-8 of the present invention and Comparative Examples 1-5 were tested for performance, and the results are shown in Table 1.

[0139] in:

[0140] The test method for the alkaline boiling resistance stability is as follows: on the surface of an aluminum plate sprayed and cured with epoxy primer, polyurethane mid-coat and white polyurethane topcoat, the coatings (clear varnishes) of Examples 5-8 of the present invention and Comparative Examples 1-5 are sprayed respectively to prepare a coating with a dry film thickness of 20 μm for the clear varnish. After curing at 50°C for 2 hours, the coating is placed in a 5% by mass sodium hydroxide aqueous solution and boiled at 100°C for 5 hours. The changes in the surface free energy and the water contact angle of the coating before and after boiling are tested.

[0141] The test method for self-cleaning performance is as follows: 2 grams of printer black toner is evenly sprinkled on the surface of an aluminum plate with an area of ​​5cm×10cm and a coating with a coating thickness of 20μm. The plate is placed at an inclination angle of about 10°. Tap water is sucked with a straw and dripped on the coating surface at a certain height. The ability of the water droplets to carry away the toner during the rolling process is divided into 0-5 levels, where level 0 means that all toner is removed, level 1 means that the toner removal amount is between 80-100%, level 2 means that the toner removal amount is between 60-80%, level 3 means that the toner removal amount is between 40-60%, level 4 means that the toner removal amount is between 20-40%, and level 5 means that the toner removal amount is <20%.

[0142] Table 1: Comparison of coating performance test results prepared in Examples 5-8 and Comparative Examples 1-5

[0143]

[0144]

[0145] As shown in Table 1, the coatings prepared in Examples 5-8 of the present invention all have high hardness, high gloss, anti-fouling self-cleaning, weather resistance and anti-corrosion, and the surface energy of the paint film is <25mN / m, which is a low surface energy coating; the dynamic friction coefficient is extremely low, between 0.02-0.03, which is better than 0.04-0.1 of Teflon coating, and the dynamic friction coefficient is one order of magnitude lower than that of conventional organic coatings, which is a super-slip coating. The relevant properties are all significantly better than those of Comparative Examples 1-5, among which:

[0146] (1) The coatings prepared in Examples 5-8 of the present invention exhibit excellent initial low surface energy, low adhesion and film stability. Among them: the initial surface energy is between 20.6mN / m-21.9mN / m, and it exhibits excellent stability. Taking Example 6 as an example, its alkaline boiling stability and surface free energy after 24 months of outdoor exposure increased from the initial 20.6mN / m to 22.1mN / m and 23.0mN / m, respectively, which is still a low surface energy coating; compared with the initial water contact angle of 106.5° (see Figure 2 ), its alkaline boiling stability and the water contact angle of the outdoor hanging board after 24 months only decreased to 104.7° and 102.6°, respectively, which were still greater than 100°, and the water drop effect was significant; in addition, the coatings prepared in Examples 5-8 also showed excellent weather resistance, anti-corrosion properties and mechanical properties.

[0147] (2) Compared with Example 6 of the present invention, the coating of Comparative Example 1 is prepared by using a short carbon chain silicone epoxy co-modified acrylic resin to replace the long chain alkyl and silicone co-modified amino acrylic resin of Example 2. First, compared with the long carbon chain and silicone co-modified amino acrylic resin in Example 2, the short carbon chain silicone modified acrylic resin has poor compatibility with the long chain alkyl modified hydrogen silicone oil and the long chain alkyl modified polysilazane in the coating system, and there is a phase separation problem in the coating, resulting in the coating cross-linking and curing being unpredictable, which seriously reduces the gloss, density and protectiveness of the coating; secondly, it can be seen from the cupping test and impact resistance results that the amino group in the long chain alkyl and silicone co-modified amino acrylic resin used in Example 2 provides catalytic activity and adhesion promotion, and synergizes with the long chain alkyl to improve the flexibility of the coating. Furthermore, Example 6 can obtain a high-hardness, high-density and high-gloss coating by directly curing at room temperature of 35°C for 30 minutes. The coating remains intact after the MEK resistance test is more than 300 times. The coating in Comparative Example 1 is first dried at room temperature for 1 hour, and then the paint film is cured at 160°C for 1 hour. The 20° glossiness of the prepared coating is only 72.4°, which is much less than 102.7° of Example 6. The self-cleaning performance is level 3, which is far less than level 1 of Example 6. The coating is destroyed after the MEK resistance test is more than 41 times. Combined with the results of the water boiling resistance test, it is shown that the coating of Comparative Example 1 has a low degree of curing, poor reaction crosslinking and density, and weak protection ability for the substrate. The comprehensive results show that the amino acrylic resin co-modified by the long-chain alkyl and silicone in Example 2 of the present invention can effectively improve the room temperature curing speed of the coating and promote the adhesion of the substrate. The prepared coating can be cured at room temperature to obtain a highly dense weather-resistant self-cleaning antifouling coating. Correspondingly, the surface properties and various mechanical properties of the coating prepared by using short carbon chain silicone modified acrylic resin are much lower than those of the coating prepared by the present invention.

[0148] (3) Compared with Example 6 of the present invention, the coating of Comparative Example 2 was prepared by using methyl hydrogen silicone oil instead of long-chain alkyl modified hydrogen silicone oil. Methyl hydrogen silicone oil has low surface energy and lacks the effect of long-chain alkyl, resulting in poor system compatibility with acrylic resin. Phase separation occurs during the curing process of the coating, resulting in poor compactness and hydrophobicity of the coating. The initial surface energy is greatly increased from 20.6 mN / m in Example 6 to 35.6 mN / m, which is much higher than the requirement of less than 25 mN / m for low surface energy surfaces; the initial contact angle with water is reduced from 106.5° in Example 6 to 76.8°; the glossiness is greatly reduced, and its 20° glossiness is reduced from 102.7° in Example 6 to 43.5°, indicating that the components of the coating are not evenly distributed, and it is impossible to effectively cure to obtain a flat and dense protective film and effectively protect the substrate.

[0149] (4) Compared with Example 7 of the present invention, Comparative Example 3 does not add hyperbranched silicone resin, and the various properties of the coating are greatly reduced, especially its dynamic friction coefficient, which is increased from 0.023 in Example 7 to 0.381; at the same time, the water resistance of the coating is significantly reduced, especially after alkaline boiling and outdoor exposure, its water contact angle is greatly reduced to 74.2° and 69.6°, respectively, which is far lower than the requirement of more than 90° for hydrophobic coating. At the same time, the artificial climate accelerated test resistance and salt spray resistance of Comparative Example 3 are also far lower than the level of 4000h in Example 7 of the present invention, indicating that the hyperbranched resin synergizes with the silane coupling agent in the formulation system, promotes better film formation of the resin, effectively improves the density, smoothness and optical properties of the resin, and reduces the dynamic friction coefficient of the coating.

[0150] (5) Compared with Example 7 of the present invention, Comparative Example 4 does not add polysilazane, and uses methyl hydrogen silicone oil instead of long-chain alkyl modified hydrogen silicone oil. The obtained coating has poor weather resistance, and the transmittance, surface properties and mechanical properties are far inferior to those of Example 7. This is mainly because the methyl hydrogen silicone oil has poor system compatibility with the resin due to the lack of long-chain alkyl groups and the difference in surface energy, and the two cannot achieve compatibility and effective cross-linking film formation. In addition, polysilazane also synergizes with the resin and long-chain alkyl modified hydrogen silicone oil in the system, greatly improving the reaction speed and cross-linking density of the system, improving the surface and mechanical properties of the coating, and achieving weather-resistant self-cleaning and long-acting antifouling effect.

[0151] (6) Compared with Example 7 of the present invention, the coating of Comparative Example 5 uses perhydropolysilazane instead of long-chain alkyl-modified polysilazane during preparation. Although the hardness of the coating prepared by this method can also be 5H, the flexibility of the coating is poorer than the adhesion of the substrate, and the cupping test is only 2.6mm, which is much lower than the 7.4mm of the embodiment. The coating is broken under the impact of 1 kg gravity at a height of 20cm, while the coating of Example 7 remains intact under the impact of 1 kg gravity at a height of 50cm. Secondly, the coating surface prepared in Comparative Example 5 has poor self-cleaning performance, with a surface free energy of 34.8 mN / m, which is much higher than the requirement of less than 25 mN / m for low surface energy surfaces and 20.7 mN / m in Example 7; the initial water contact angle is reduced from 105.1° in Example 7 to 95.3°, the stain resistance is greatly improved from 0.5% in Example 7 to 15.2%, and the self-cleaning grade is improved from level 1 in Example 7 to level 3; furthermore, the coating prepared in Comparative Example 5 has poor protective performance and fails to pass the 10% NaOH alkali resistance test, boiling resistance, heat resistance and salt spray resistance test. This is because the perhydropolysilazane has a single structure, high Si-H content and NH content, and lacks Si-CH 3 and Si-long-chain alkyl, so its hydrophobic self-cleaning performance is far inferior to the coating obtained by using long-chain alkyl-modified polysilazane; in addition, due to the lack of long-chain alkyl and Si-CH 3The compatibility of perhydropolysilazane with key components such as resin and long-chain alkyl-modified hydrogen-containing silicone oil in the system is poor. Si-H and NH in perhydropolysilazane are difficult to react completely and remain in the system. The resulting coating is brittle and lacks flexibility. The coating has large internal stress, is brittle, and has poor impact resistance. After the coating is subjected to high temperature, only the hard -Si-N- group of perhydropolysilazane remains, lacking the low surface energy and flexible Si-CH 3 and Si-long chain alkyl, so the coating has low slipperiness and a friction coefficient of only 0.266, which is an order of magnitude larger than 0.023 in Example 7. This solution cannot meet the surface requirements of low surface energy super-slip coatings.

[0152] In summary, the coatings prepared in Examples 5-8 of the present invention adopt organic-inorganic hybrid technology to obtain a high-density coating with a pencil hardness of 6-7H, which greatly improves the wear resistance and scratch resistance of the coating. At the same time, the resin with a specific structure, the long-chain alkyl-modified hydrogen-containing silicone oil and the long-chain alkyl-modified polysilazane enhance the flexibility and hydrophobic antifouling property of the coating; the introduction of the aminoacrylic acid monomer in the aminoacrylic acid resin co-modified by the long-chain alkyl and silicone can effectively increase the room temperature curing speed of the coating and promote the adhesion of the substrate. The prepared coating can be cured at room temperature to obtain a highly dense weather-resistant self-cleaning antifouling coating; by introducing Si-H bonds and NH bonds, the silane coupling agent and polysilazane are co-polymerized to form a film, and the two interact with each other to enhance the reaction speed and crosslinking density of the coating system under the action of moisture; by introducing a large amount of Si-CH 3 And Si-long-chain alkyl groups, effectively improve the thermal stability, high and low temperature resistance, impact resistance, stain resistance and water resistance of the coating, reduce the refractive index of the coating, obtain high hardness and weather resistance, excellent low adhesion characteristics, scratch resistance and wear resistance, low surface roughness and high gloss on the painted surface, realize permanent anti-fingerprint function on the surface of electronic screens, fully meet the requirements of photovoltaic panels, wind turbine blades, EMU locomotives, security cameras in outdoor windy and sandy environments with high requirements for resistance to foreign object impact, as well as smart appliance screens, marble tea tables, floor ceramics, stainless steel sinks, non-stick pans, bathrooms, etc., which have high requirements on material surface hardness and urgent needs for self-cleaning and anti-fouling of material surfaces and safe and fluorine-free, and can achieve long-term anti-fouling and self-cleaning effects.

[0153] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A resin, characterized in that The raw material components of the resin include, by weight: 2-10 parts of a first monomer, 25-40 parts of a second monomer, 3-20 parts of a third monomer, 0.5-1 parts of an initiator, 0.1-0.5 parts of a chain transfer agent, and 46-50 parts of a first solvent; the first monomer is an amino acrylic acid monomer, the second monomer is a long-chain acrylate monomer, and the third monomer is a silicone monomer.

2. The resin according to claim 1, characterized in that The aminoacrylic acid monomer is at least one selected from tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, dipropylaminoethyl methacrylate, diisopropylaminoethyl methacrylate, dibutylaminoethyl methacrylate, and di-tert-butylaminoethyl methacrylate; And / or, the long-chain acrylate monomer is selected from at least one of n-octyl methacrylate, n-octyl acrylate, isooctyl methacrylate, isooctyl acrylate, isobutyl methacrylate, isobutyl acrylate, lauryl methacrylate, lauryl acrylate, isotridecyl methacrylate, isotridecyl acrylate, heptadecyl methacrylate, heptadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, and behenyl acrylate; And / or, the silicone monomer is selected from at least one of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-acetoxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane and 3-(isomethacryloxy)propyltri(trimethylsiloxane)silane.

3. The resin according to claim 1 or 2, characterized in that The initiator is selected from at least one of 2,2'-azobis(2-methylpropionitrile) and 2,2'-disazo-(2,4-dimethylvaleronitrile); And / or, the chain transfer agent is at least one selected from n-dodecyl mercaptan, secondary dodecyl mercaptan, tert-dodecyl mercaptan, cyclohexyl mercaptan, isooctyl 3-mercaptopropionate, n-butyl 3-mercaptopropionate, n-octyl mercaptan, mercaptoethanol, and thioglycolic acid; And / or, the first solvent is selected from at least one of ether solvents, ester solvents, and ketone solvents.

4. A method for preparing a resin according to any one of claims 1 to 3, characterized in that: The following steps are involved: The first solvent and the initiator are divided into three parts respectively, and one part of the first solvent and one part of the initiator are first mixed and heated; then another part of the first solvent, another part of the initiator, the first monomer, the second monomer and the third monomer are added to react; then the remaining first solvent and the remaining initiator are added to continue the reaction; finally, a chain transfer agent is added, the temperature is lowered, and the resin is obtained.

5. The method for preparing the resin according to claim 4, characterized in that: The heating temperature is 75-80°C; and / or the cooling temperature is 20-30°C.

6. A coating, characterized in that: The raw material components of the coating include, by weight: 10-20 parts of the resin according to any one of claims 1 to 3, 10-20 parts of long-chain alkyl-modified hydrogenated silicone oil, 10-30 parts of silane coupling agent, 1-3 parts of hyperbranched silicone resin, and 0.3-2 parts of long-chain alkyl-modified polysilazane.

7. The coating according to claim 6, characterized in that The structural formula of the long-chain alkyl modified hydrogen-containing silicone oil is shown in formula (1): In formula (1): x=0-500, y=1-500, z=1-25; P is selected from a C8-C18 straight chain alkyl group, a C8-C18 branched chain alkyl group, a C8-C18 cycloalkyl group or a C8-C18 aralkyl group; And / or, the silane coupling agent is selected from at least one of tetraethyl silicate, tetramethyl silicate, trimethoxysilane, triethoxysilane, vinyl triisopropoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl triisopropoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-glycidyloxypropyl triisopropoxysilane, octyl trimethoxysilane, octyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, octadecyl trimethoxysilane, octadecyl triethoxysilane, and long-chain quaternary ammonium salt silane; the structural formula of the long-chain quaternary ammonium salt silane is shown in formula (2): In formula (2): R1 is selected from a C8-C18 alkyl group, and R2 is selected from CH3 or CH2CH3; And / or, the structural formula of the hyperbranched silicone resin is as shown in formula (3): In formula (3): R is at least one selected from γ-glycidyloxypropyl, γ-aminopropyl, and hydrogen; And / or, the structural formula of the long-chain alkyl-modified polysilazane is as shown in formula (4): In formula (4): a=3-500, b=3-500, c=1-100; R3 is selected from a C8-C18 straight chain alkyl group or a C8-C18 branched chain alkyl group.

8. A method for preparing a coating as claimed in claim 6 or 7, characterized in that: The following steps are involved: The various raw materials for preparing the coating are mixed to obtain the coating.

9. A coating, characterized in that: The coating is formed by curing the coating according to claim 6 or 7.

10. Use of the coating according to claim 6 or 7, or the coating according to claim 9 in the fields of construction, new energy, transportation, home furnishing, communication or mechanical equipment.

Citation Information

Cited By

  • Special high-temperature-resistant and high-light-transmittance silica gel lens for vehicle lamp and preparation method thereof

    CN120737613A

  • High-wear-resistance antifouling normal-temperature curing polysilazane coating as well as preparation method and application thereof

    CN122104054A

  • A high-wear-resistant and stain-resistant room-temperature curing polysilazane coating, its preparation method and application

    CN122104054B